2004
DOI: 10.1128/jvi.78.24.13769-13778.2004
|View full text |Cite
|
Sign up to set email alerts
|

Human Papillomavirus Type 16 E6 Promotes Retinoblastoma Protein Phosphorylation and Cell Cycle Progression

Abstract: We show that E6 proteins from benign human papillomavirus type 1 (HPV1) and oncogenic HPV16 have the ability to alter the regulation of the G 1 /S transition of the cell cycle in primary human fibroblasts. Overexpression of both viral proteins induces cellular proliferation, retinoblastoma (pRb) phosphorylation, and accumulation of products of genes that are negatively regulated by pRb, such as p16INK4a , CDC2, E2F-1, and cyclin A. Hyperphosphorylated forms of pRb are present in E6-expressing cells even in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
34
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 25 publications
4
34
0
Order By: Relevance
“…Malanchi et al (12,26) reported that HPV16 E6 could induce cellular proliferation, pRb phosphorylation, and accumulation of gene products that are negatively regulated by pRb, such as p16, cdc2, E2F-1, and cyclin A. Consistent with the hyperphosphorylated state of pRb, cyclin A/cdk2 activity is highly elevated in cells expressing E6 from either HPV16 or HPV18.…”
Section: Cancer Researchsupporting
confidence: 50%
“…Malanchi et al (12,26) reported that HPV16 E6 could induce cellular proliferation, pRb phosphorylation, and accumulation of gene products that are negatively regulated by pRb, such as p16, cdc2, E2F-1, and cyclin A. Consistent with the hyperphosphorylated state of pRb, cyclin A/cdk2 activity is highly elevated in cells expressing E6 from either HPV16 or HPV18.…”
Section: Cancer Researchsupporting
confidence: 50%
“…The cyclin-dependent kinase (CDK) inhibitor p21 WAF1/CIP1 (p21) is the target of the HPV E6 oncoprotein (6,7). Induction of p21 by p53-dependent (8) or p53-independent pathways (9, 10) results in the inhibition of cyclin/CDK complexes that regulate cellular proliferation (11,12).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Katori et al [27] described a significant decrease of immunoexpression of Moreover, Malanchi et al [36,37] clearly demonstrated that HPV E6 may strongly down-regulate p21waf1/cip1. In contrast to our results, Altavilla et al [26] showed stronger p21waf1/cip1 immunoexpression in HPV-positive sinonasal inverted papillomas, and Hafkamp et al [38] demonstrated that HPV positivity was strongly correlated with p21waf1/ /cip1 overexpression in tonsillar squamous cell carcinomas.…”
Section: Discussionmentioning
confidence: 99%
“…The literature data suggests that overexpression of p16INK4a and cyclin D1 is strongly related to the presence of HPV16/18. According to Malanchi et al [36,37], HPV16 E6 could induce accumulation of p16 and cellular proliferation. König et al [41] demonstrated a statistically significant relationship between the presence of HPV16/18 DNA and increased immunoexpression of p16INK4a in head and neck squamous cell cancers, but the HPV 6/11 presence was also significantly correlated with p16INK4a immunoreactivity.…”
Section: Discussionmentioning
confidence: 99%